1993
DOI: 10.1093/carcin/14.12.2559
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the chemotherapeutic drug VP-16 on poly(ADP-ribosylation) in apoptotic HeLa cells

Abstract: We have studied the effect of the chemotherapeutic drug VP-16 (etoposide) on the metabolism of HeLa cells by analysing different cellular parameters; in particular we have focused on changes in cellular morphology that are considered as markers of apoptosis. By immunofluorescence experiments we have shown that VP-16 causes the complete disruption of nucleoli and induces chromatin margination and fragmentation. Agarose gel electrophoresis of DNA from cells treated with 10-100 microM VP-16 showed the appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…From previous studies it would appear that etoposide-induced PARP activation is dependent not only on the concentration and schedule of etoposide exposure, but also on the cell type. For example, etoposide has been found to activate PARP in HL-60, U939 and HeLa cells but not Molt 4 and CEM cells (Tanizawa et al, 1989;Kubota et al, 1990;Negri et al, 1993;Bernardi et al, 1995). Together, the failure of NU1025 to enhance etoposide cytotoxicity or DNA strand breakage, and the lack of PARP activation following etoposide treatment, indicate that PARP is not involved in etoposide cytotoxicity in L1210 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous studies it would appear that etoposide-induced PARP activation is dependent not only on the concentration and schedule of etoposide exposure, but also on the cell type. For example, etoposide has been found to activate PARP in HL-60, U939 and HeLa cells but not Molt 4 and CEM cells (Tanizawa et al, 1989;Kubota et al, 1990;Negri et al, 1993;Bernardi et al, 1995). Together, the failure of NU1025 to enhance etoposide cytotoxicity or DNA strand breakage, and the lack of PARP activation following etoposide treatment, indicate that PARP is not involved in etoposide cytotoxicity in L1210 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that secondary fragmentation of DNA during apoptosis may induce PARP (Negri et al, 1993). To investigate if apoptotic DNA cleavage was responsible for the observed effects of camptothecin and etoposide on PARP activity, morphological examination of Hoechst 33258-stained cells was conducted.…”
Section: Induction Of Apoptosis By Camptothecin and Etoposidementioning
confidence: 99%
“…There are several characteristic cellular and biochemical hallmarkers of apoptotic cell death, including oligonucleosomal DNA fragmentation, 45 nucleus condensation, DNA laddering, and PARP-1 cleavage. 46,47 The sequence of changes in cellular morphology of apoptosis can be summed up as (1) cell shrinkage (2) condensation, margination and fragmentation of chromatin and (3) retention of cytoplasmic organelle structure, but loss of positional interrelationships of organelles.…”
Section: Minimum Inhibitory Concentration Measurementsmentioning
confidence: 99%
“…After a 3-h treatment with 100 M VP-16, cells were allowed to recover for 3 or 24 h in normal medium before being analyzed by Western blotting to assess the phosphorylation status of hLigI. Because VP-16 is a well known apoptotic agent (Negri et al, 1993;Kaufmann, 1998), in parallel we determined the occurrence of apoptosis by following different morphological parameters such as nuclear condensation and fragmentation. A very low level of apoptosis (3.5 Ϯ 0.1%) was detectable at the end of the 3-h treatment with VP-16.…”
Section: Dephosphorylation Of Hligi In Response To Dna Damagementioning
confidence: 99%